Penerapan Akad Al-Qardh Pada Koperasi Pojok Syariah Cileunyi Bandung Kesesuaiannya Dengan Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia - Khotimah Damayanti; Rima Elya Dasuki; Nanang Sobarna (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2022)
Al-Qardh is a type of loan given to parties who need assistance in urgent circumstances for a certain period of time without having to pay interest or profit. The loan of al-Qardh's contract is adjusted to the perspective of DSN-MUI Fatwa No: 19/DSN-MUI/IV/2001 concerning Al-Qardh. Therefore, this study aims to determine the application of the Al-Qardh contract, conformity to the perspective of DSN-MUI Fatwa No: 19/DSN-MUI/IV/2001, and to know the efforts made by the Koperasi Pojok Syariah to be in accordance with the fatwa perspective. The research method used is descriptive analysis with a qualitative approach through observation and also interviews with informants to be able to describe the mechanism for implementing the Al-Qardh contract. The results showed that the Koperasi Pojok Syariah generally implemented the Al-Qardh agreement in accordance with DSN-MUI Fatwa No: 19/DSN-MUI/IV/ 2001. However, there needs to be a stage that must be recommended in the contractual mechanism in the Al-Qardh contract loan.